The Role of Islamic Reality Therapy Intervention to Reduce the Academic Burnout of High-School Students - Prawitasari, Galuh; Rahman, Fathur; Candra, Vikistha Dimas (Universitas Muhammadiyah Yogyakarta, 2024)
Academic burnout is one of the academic stressors that adolescents often experience. Academic burnout without intervention may affect students' psychological state and learning achievement. This study aims to reduce students’ academic burnout through Islamic reality therapy group guidance services. The research subjects consisted of 12 students of class XI who had pretest scores of academic burnouts in the high category. The research method used is classroom action research with two cycles. Data were analyzed with descriptive statistical techniques. The preliminary study results showed that students have an average academic burnout score of 49.17, classified as the high category. In the first cycle, the average student’s academic burnout score is reduced by 7.83 points to 41.33 compared to the preliminary result. In the second cycle, the average academic burnout score decreased by 1.83 points to 39.5 compared to the former cycle's average score. This shows that Islamic reality therapy has been shown to reduce students’ academic burnout.